2020
DOI: 10.25134/ieflj.v6i2.3384
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Video Recording as a Learning Tool to Improve Indonesian Efl Students� Speaking Performance

Abstract: This research attempts to reveal the effectiveness of using smartphone video recording as an English learning tool to improve the students� speaking performance and the students� interest in using the tool in speaking learning process. All participants were second-grade students of private boarding school in Makassar, Indonesia. This research was conducted through quasi experimental study design with two groups comprises of 25 students in the experimental group and 25 students in the control group. The instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Furthermore, it is necessary to look for tools that are going to allow students to create their videos. For instance, Dzakiah et al (2020) conducted a study in which it was demonstrated that students' performance in terms of fluency and comprehension improved through the use of cell phone video recording. Students had to record videos speaking about past events and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is necessary to look for tools that are going to allow students to create their videos. For instance, Dzakiah et al (2020) conducted a study in which it was demonstrated that students' performance in terms of fluency and comprehension improved through the use of cell phone video recording. Students had to record videos speaking about past events and activities.…”
Section: Introductionmentioning
confidence: 99%